Electoral Expression With Institutional Bounds: Framing Judicial Treatment of Elections in New Zealand - Bullock, David (Victoria University of Wellington Law Review, 2011)
This article explores the way in which the courts have treated cases involving electoral broadcasting in New Zealand. Cases involving electoral broadcasting have been decided on a range of approaches. This article uses an "institutional" conception of elections to determine whether certain bounds can be drawn to define a category of election expression, comprising certain rules and norms, which the courts can use when dealing with expression around elections. New Zealand's case law to date is broadly consistent with an institutional model of electoral expression within which a higher level of judicial scrutiny of broadcasters is exhibited. This paper proposes that an express recognition of this institutional conception would provide some clarity and unity to decisions involving the sensitive issue of electoral broadcasting.